Modelling the accumulation of 137Cs by Atlantic bluefin tuna (Thunnus thynnus) after a hypothetical nuclear accident in the Northwest Atlantic Ocean - Carmen Cortés; Raúl Periáñez; Barbara A. Block; Michael R. Castleton; Pablo Cermeño; Simon Dedman (Journal of Marine Systems, 2026)

Numerical modelling of radionuclide uptake by bluefin tuna along its migration routes in the Mediterranean Sea after a nuclear accident - Carmen Cortés; Raúl Periáñez; Barbara A. Block; Michael R. Castleton; Pablo Cermeño; Simon Dedman (Marine Environmental Research, 2024)

Tagging of Atlantic bluefin tuna off Ireland reveals use of distinct oceanographic hotspots - Camille M.L.S. Pagniello; Niall Ó Maoiléidigh; Hugo Maxwell; Michael R. Castleton; Emilius A. Aalto; Jonathan J. Dale; Robert J. Schallert; Michael J.W. Stokesbury; Ronán Cosgrove; Simon Dedman; Alan Drumm; Ross O'Neill; et al. (Progress in Oceanography, 2023)

Assignment of tracks from tagged Atlantic bluefin tuna Thunnus thynnus to potential stocks using behavioural differences and habitat partitioning - Simon Dedman; Emilius A. Aalto; Michael J. W. Stokesbury; Robert J. Schallert; Michael R. Castleton; Barbara A. Block (Frontiers in Marine Science, 2023)
Introduction Atlantic bluefin tuna (ABT) are large, migratory pelagic predators of high economic importance. ABT are currently managed as two independent stocks assigned to discrete spawning areas (Gulf of Mexico, and Mediterranean); however, stock overlap outside spawning areas makes accurate assignment of catch to stock-of-origin difficult. Methods Within this two-stock paradigm, we characterised stock-specific spatial distributions and behaviours by comparing habitat usage and vertical movement behaviours of 118 electronically tagged adult ABT spatially assigned to the GOM and Med spawning grounds. These spatial and behavioural differences were used in tests to probabilistically assign unknown individuals (which did not visit the GOM/Med spawning areas) to a stock. Results This new methodological approach using existing tag data, enables increased assignment of a track to a potential stock, to be achieved before genetic assignments. We identified certain markedly different movement patterns, range extents, depth use preferences (and associated area usage), migration directness and speeds, corresponding distance from shore, and mesopelagic-layer visitation. The probabilistic assignment approach had 97% in-bag testing accuracy, then assigned 190 individuals to a stock, doubling the number of assigned stock-of-origin tracks in our dataset, and potentially revealing novel movement and behaviour patterns among pre-spawning-age ABT. Discussion This approach can be easily adapted to other study species, more stocks, and different testing variables, hopefully serving as a useful addition to the fisheries management toolkit.

Horizontal and vertical movements of juvenile bluefin tuna ( Thunnus orientalis ) in relation to seasons and oceanographic conditions in the eastern Pacific Ocean - TAKASHI KITAGAWA; ANDRE M. BOUSTANY; CHARLES J. FARWELL; THOMAS D. WILLIAMS; MICHAEL R. CASTLETON; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Electronically tagged juvenile Pacific bluefin, Thunnus orientalis , were released off Baja California in the summer of 2002. Time‐series data were analyzed for 18 fish that provided a record of 380 ± 120 days (mean ± SD) of ambient water and peritoneal cavity temperatures at 120 s intervals. Geolocations of tagged fish were estimated based on light‐based longitude and sea surface temperature‐based latitude algorithms. The horizontal and vertical movement patterns of Pacific bluefin were examined in relation to oceanographic conditions and the occurrence of feeding events inferred from thermal fluctuations in the peritoneal cavity. In summer, fish were located primarily in the Southern California Bight and over the continental shelf of Baja California, where juvenile Pacific bluefin use the top of the water column, undertaking occasional, brief forays to depths below the thermocline. In autumn, bluefin migrated north to the waters off the Central California coast when thermal fronts form as the result of weakened equatorward wind stress. An examination of ambient and peritoneal temperatures revealed that bluefin tuna fed during this period along the frontal boundaries. In mid‐winter, the bluefin returned to the Southern California Bight possibly because of strong downwelling and depletion of prey species off the Central California waters. The elevation of the mean peritoneal cavity temperature above the mean ambient water temperature increased as ambient water temperature decreased. The ability of juvenile bluefin tuna to maintain a thermal excess of 10°C occurred at ambient temperatures of 11–14°C when the fish were off the Central California coast. This suggests that the bluefin maintain peritoneal temperature by increasing heat conservation and possibly by increasing internal heat production when in cooler waters. For all of the Pacific bluefin tuna, there was a significant correlation between their mean nighttime depth and the visible disk area of the moon.